Relationship between Undernutrition and Anemia in Patients with Ulcerative Colitis - Yury P. Uspenskiy; Sergei V. Ivanov; Alexander S. Krasichkov; Michael M. Galagudza; Yulia A. Fominykh (Gastroenterology Insights, 2022)
This study aimed to assess the relationship between malnutrition and anemia in patients with ulcerative colitis (UC). The cross-sectional retrospective study included 80 patients with UC. Body mass index and total body fat mass were derived retrospectively from bioimpedance measurements. Anemia was diagnosed retrospectively according to WHO criteria. A binary logistic regression was performed to study the relationship between nutritional status parameters and anemia, and adjusted for demographic and disease-associated characteristics. The prevalence of anemia in the study population was 40.0%. Among all included patients, 86.3% had acute disease corresponding to S1–S3 disease behavior. In the adjusted binary logistic model, total serum protein level below 64 g/L and low body fat percentage were associated with high odds for the of development of anemia, with odds ratios of 5.1 (95% CI 1.5; 17.8; p = 0.01) and 8.5 (95% CI 1.1; 63.6; p = 0.037), respectively. The adjusted model included sex, age, disease activity, extent of gut involvement, quantity of relapses from disease onset, and treatment with immunosuppressive drugs as confounders. Hypoproteinemia and low body fat percentage were associated with anemia in patients with UC. These results suggested that undernutrition may be involved as one of the causative factors of anemia in UC.